How geometry task management shapes students’ spatial structuring: Evidence from tangram-based pythagorean problem solving - Yudianto, Erfan; Firmansyah, Frenza Fairuz; Zulnaidi, Hutkemri (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purpose: This study examines how geometry task management shapes students’ spatial structuring when solving Pythagorean Theorem problems through tangram-based tasks. Method: This study employed a qualitative case study design involving six eighth-grade students (aged 13–14) from a public junior high school. The participants were purposively selected to represent diverse levels of classroom participation. Data were collected across three classroom sessions through students’ work artifacts, classroom interaction transcripts, and observation notes. Data were analyzed using a qualitative interpretative approach involving iterative coding and cross-case comparison to identify patterns of spatial structuring, particularly in relation to part–whole coordination, recognition of invariant properties, and reconfiguration strategies. Findings: The analysis indicates that geometry task management shapes students’ spatial structuring through geometric reconfiguration and increasing attention to part–whole relationships. Students’ reasoning evolves from visual manipulation toward more relational forms of understanding as tasks are sequenced and supported through teacher questioning; for example, some students initially relied on visual fitting strategies but later justified their rearrangements by referring to equal lengths and area equivalence after teacher prompts. The results indicate that spatial reasoning emerges through interaction with representations and is influenced by how instructional tasks direct students’ attention to invariant geometric relationships. Significance: This study contributes to mathematics education by showing how spatial structuring can be understood as a pedagogically supported process shaped through geometry task management. The findings highlight the importance of task sequencing and teacher guidance in supporting students’ spatial reasoning in learning the Pythagorean Theorem.